1996
DOI: 10.1007/bf01806183
|View full text |Cite
|
Sign up to set email alerts
|

Demonstration of silver-stained nucleolar organizer region associated proteins (AgNORs) after wet autoclave pretreatment in breast carcinoma: Correlation to tumor stage and long-term survival

Abstract: Argyrophilic nucleolar organizer region associated proteins (AgNORs) are known to reflect cellular and nucleolar activity. Due to a novel staining procedure, which substantially improves visualisation of AgNORs on formalin-fixed and paraffin-embedded material, AgNORs can be reliably demonstrated as true substructures of the nucleoli. The aim of the present study was to apply a standardized morphometric AgNOR quantification on a large series of breast carcinomas with regard to its prognostic relevance. AgNOR qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
7
0

Year Published

1996
1996
2001
2001

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 32 publications
4
7
0
Order By: Relevance
“…Furthermore, the introduction of the coefficient of variation (CV) of simultaneously measured number and area of AgNORs per nucleus provides a highly reproducible parameter of AgNOR analysis. 36 With regard to clinical significance, the outstanding performance of standardized AgNOR analysis in predicting the clinical course of the respective patients independently from established prognostic factors has been proven so far in colorectal, 37 breast, 38 and lung cancer, 39 as well as in OSCCs (if assessed at the invasive tumour front), as demonstrated in the present and previous works. 23,40 Finally, the cost of silver staining is lower than that of most immunohistochemical reactions generally used in tumour diagnostics.…”
Section: Discussionsupporting
confidence: 57%
“…Furthermore, the introduction of the coefficient of variation (CV) of simultaneously measured number and area of AgNORs per nucleus provides a highly reproducible parameter of AgNOR analysis. 36 With regard to clinical significance, the outstanding performance of standardized AgNOR analysis in predicting the clinical course of the respective patients independently from established prognostic factors has been proven so far in colorectal, 37 breast, 38 and lung cancer, 39 as well as in OSCCs (if assessed at the invasive tumour front), as demonstrated in the present and previous works. 23,40 Finally, the cost of silver staining is lower than that of most immunohistochemical reactions generally used in tumour diagnostics.…”
Section: Discussionsupporting
confidence: 57%
“…In the present study, an independent prognostic relevance of the pT stage could be shown exclusively with regard to the prediction of locoregional recurrences ( Table 2). The usefulness of standardized AgNOR parameters as independent predictors of prognosis has been demonstrated recently in different human malignancies (Ofner et al, 1995b;Totsch et al, 1995;Ofner et al, 1996). In a previous study, we could show a significant increase of the AgNOR content at the invasive front of British Journal of Cancer (1997) oral squamous cell carcinomas compared with central parts of the tumours and non-tumorous mucosa (Piffko et al, 1996).…”
Section: Discussionsupporting
confidence: 51%
“…AgNORs are considered to reflect biosynthetic and nucleolar activity of a cell and thus serve as indicators of the rapidity of the cell cycle (Trere et al, 1989;Derenzini et al, 1994). Using a recently introduced standardized silver staining and morphometric analysis in archival histological material (Ofner et al, 1994(Ofner et al, , 1995a, the independent prognostic value of AgNORs has been established in colonic, lung and breast cancer (Ofner et al, 1995b;Totsch et al, 1995;Ofner et al, 1996).…”
mentioning
confidence: 99%
“…As recently reviewed, also the analysis of the silver-stainable nucleolar organizer regions (AgNORs) has been frequently found to be prognostically useful [35]. The standardization of the conventional staining procedure [37] by the introduction of wet autoclaving in 1994 [32,31] has especially improved the meaning of AgNOR analysis, and different studies on the prognostic significance of this new staining protocol have been reported since then on carcinoma of the breast [34], oral cavity [36], lung [48], stomach [17,39], prostate [9], and colorectum [16,33]. However, the analysis of either the MIB-1 immunoreactivity or the amounts of AgNOR describes a static situation only.…”
Section: Introductionmentioning
confidence: 99%